Effectiveness of Drug Treatments for Lowering Uric Acid on Renal Function in Patients With Chronic Kidney Disease and Hyperuricemia: A Network Meta-Analysis of Randomized Controlled Trials - Liu, Xiang; Qiu, Yuxuan; Li, Duohui; Tan, Jiaxing; Liang, Xiuping; Qin, Wei (Frontiers in Pharmacology, 2021)
Backgrounds. Hyperuricemia is very common in patients with chronic kidney disease patients (CKD); the role of hyperuricemia in the occurrence and progression of kidney disease remains an interesting and unresolved issue for nephrologists, whether urate-lowering therapy (ULT) is warranted in CKD patients is still in controversy. To summarize and compare the clinical outcomes and adverse events (AEs) of three common ULT drugs, we performed a systematic review and network meta-analysis of randomized clinical trials (RCTs). Methods. The PubMed, MEDLINE, Clinical Trials.gov, EMBASE, and the Cochrane Central Register of Controlled Trials electronic databases were searched. The network meta-analysis was performed using the “gemtc 0.8-7” and its dependent packages in R software. The primary outcome was the change of renal function and uric acid; creatinine, proteinuria, blood pressure, adverse events were assessed as the secondary outcomes. Results. 16 RCTs involving 1943 patients were included in the final network analysis. Febuxostat, allopurinol, and benzbromarone were not found to exert superior effects over placebo upon renoprotective effect. With respect to lowering urate, the three drugs showed to be statistically superior to placebo, while febuxostat could better lower urate compared with allopurinol (MD: −1.547; 95%CrI: −2.473– −0.626). It is also indicated that febuxostat was superior to placebo at controlling blood pressure, while no differences were shown when compared allopurinol and benzbromarone to placebo. These results are stable in subgroup analysis. Conclusion. There is insufficient evidence to support the renoprotective effects of the three urate-lowering agents in CKD patients with hyperuricemia; febuxostat shows a tendency to be superior than allopurinol on lowering the decline of eGFR and increment of proteinturia, but the difference does not reach a statistical significance. Regarding its urate-lowering effect, febuxostat appears to be a satisfactory alternative to allopurinol and benzbromarone, and can control blood pressure better.